ANALISIS OPTIMALISASI PENJUALAN FURNITURE MELALUI LINIER PROGAMMING DENGAN METODE SIMPLEKS PADA PT CAHAYA SAKTI MULTI INTRACO BOGOR - Prasetya, Syarief Gerald (Jurnal Ilmiah Binaniaga, 2012)
PT. Cahaya Sakti Multi Intraco is a trading company engaged in the procurement of furniture has a variety of types and a variety of brands. In the course of his business face several obstacles in planning the allocation handling products. From one brand alone was encountered problems in the combination of the products offered. Olympic brand is the core product to penetrate the domestic furniture market. Fluctuations in demand for goods erratic from one period to another period resulted in a shortage or oversupplyProducts PT Cahaya Sakti Multi Intraco ie Kitchen Set ( KS ), Cabinet Decorative ( LH ), Wardrobe ( LP ), Desk Study ( MB ) and other furniture products ( OT ). There are several obstacles in the selling of each of these products are: 1 ). The type of vehicle ( truck ) is used to fit furniture consisting of a capacity of 5,500 kgs ( Ants ) , 10,500 kgs ( Elephant ) , 13,500 kgs ( Container 20 ' feet ) , 15,000 kgs ( Double ankle ) , and 27,000 kgs ( Container 40 " feet / Tronton ) . 2 ) Maximum capacity warehouse Branch consisting of : A maximum value of 700 million ( Small Branch ) . 1,000 million ( Branch Intermediate ) , 1.600 million ( Big Branch ) . 3 ). Request for furniture products : KS as much as 4,200 units , as many as 2,600 units LH , LP as many as 11,500 units , as many as 5,200 units of MB and OT . as many as 7,000 units . Discussion of the results obtained by a linear function which aims to maximize sales ie sales = 363 X1 + 830 X2 + X3 604 + 347 + 366 X4 and X5 linear equations of the constraints that exist , namely : Freight truck type vehicle Ants = 23X1 + 8x2 + 24X3 + 22X4 +50 x5 ≤ 5,500,000 grams , Elephant = 44X1 + 15X2 + 46X3 + 43X4 +95 x5 ≤ 10,500,000 grams , Container 20 " = 56X1 + 19X2 + 59X3 + 55X4 +122 x5 ≤ 13,500,000 grams , Double ankle = 63X1 + 21X2 + 66X3 + 61X4 +135 x5 ≤ 15,000,000 grams , Container 40 " = 113X1 + 38X2 + 119X3 + 110X4 +244 x5 ≤ 27,000,000 grams and warehouse capacity Capacity Big Branch = 617X1 + 173X2 + 954X3 + 784X4 +1.0499 X5 ≤ 1,600,000,000 smu , Branch Intermediate = 386X1 + 108X2 + 596X3 + 490X4 +656 x5 ≤ 1,000,000,000 smu , and Small Branch = 270X1 + 76X2 + 417X3 + 343X4 +459 700 000 000 X5 ≤ smu , furniture Request KS ( X1 ) = ≤ 4,200 units , LH ( X2 ) = ≤ 2,600 units , LP ( X3 ) = ≤ 11,500 units , MB ( X4 ) = ≤ 5.200 , and OT ( X5 ) = ≤ 7,000 units units Total sales of Olympic brand furniture acquired PT Cahaya Sakti Multi Intraco per month is Rp . Rp 14,995,000.00 or a year . 179,940,000.00 assuming the acquisition of sales in accordance with the objective function and constraint functions remain.Keywords : optimization , sales , linear programming